THE GROWTH OF OIL PALM (Elaeis guineensis Jacq.) SEEDLING WITH DIFFERENT PLANT MEDIA AND WATERING INTERVAL - Ariyanti, Mira; Dewi, Intan Ratna; Maxiselly, Yudithia; Chandra, Yudha Arief (Jurnal Penelitian Kelapa Sawit, 2018)
Abstract Plant media is crucial factor in supporting the growth of oil palm seedling. Availability of nutrient and water within the plant media must become primary concern when providing growing media for the oil palm seedling. Suficient available water within the media can be obtained by adding organic compose and this effort is expected to increase the soil water holding capacity. This research was aimed to study the best plant media composition and watering interval giving the most positive impact to the growth of oil palm seedling. The experiment was conducted from April 2017 to August 2017 at the Experiment Station Ciparanje, Faculty of Agriculture, Padjadjaran University, Jatinangor, Sumedang Regency, West Java. The experiment used Randomized Block Design that arranged in factorial patterns with two factors. The first factor consisted of four levels of plant media composition namely plant media topsoil, subsoil:compost (1:1), subsoil:compost (1: 2), subsoil : compost (1: 3). The second fact or consisted of 3 levels of watering interval namely every day, once in two days, and once in three days. The results of experiment showed that subsoil can be made as an alternative plant media for oil palm seedling by adding compost with certain comparison accompanied by proper interval watering. The composition of plant media subsoil and compost (1:3) accompanied by watering once in 2 days produce the best growth of oil palm seedling especially its influence toward the plant heigh, diameter of trunk and dry weight of the shoot. The provision of compost in a subsoil plant media reduced the provision of water by 50%.